2013
DOI: 10.1016/j.diagmicrobio.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

The role of glycosylated epitopes in the serodiagnosis of Strongyloides stercoralis infection

Abstract: Carbohydrates of pathogen antigens have been disrupted by periodate oxidation, in order to reduce nonspecific bindings and improve serodiagnosis of parasite infections. In the present study, the enzyme-linked immunosorbent assay (ELISA) was carried out with filariform larvae antigen treated, or not treated, with sodium metaperiodate. Groups of sera from patients with Strongyloides stercoralis infection, with other intestinal parasites and a normal control, were used. The oxidation of Strongyloides stercoralis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
1
13
0
2
Order By: Relevance
“…One of the biggest hurdles in the detection of specific antibodies is the cross‐reactivity between antigens of different parasite's species, especially in areas endemic for intestinal parasites . The ELISA for the detection of specific IgG in this study showed a cross‐reactivity of 17.1%, which is within the average range of the published data …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One of the biggest hurdles in the detection of specific antibodies is the cross‐reactivity between antigens of different parasite's species, especially in areas endemic for intestinal parasites . The ELISA for the detection of specific IgG in this study showed a cross‐reactivity of 17.1%, which is within the average range of the published data …”
Section: Discussionsupporting
confidence: 88%
“…To overcome stool method limitations, serological diagnosis is often used. Nevertheless, false‐positive reactions caused by past infections or cross‐reactivity with other intestinal helminths overestimate the true prevalence of S. stercoralis infection, representing a great limitation for serologic assays . Specific IgG and IgE responses during human strongyloidiasis have been used for diagnostics, primarily for epidemiological studies and to support parasitological diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…ELISAs are the most widely used immunodiagnostic methods and have shown sensitivities and specificities above 70.0%, depending on the screened antigen and antibody isotype [101104]. However, because of difficulties in the production and the standardization of antigens capable of providing reproducible results, the use of ELISAs remains limited [30].…”
Section: S Stercoralis Diagnosis and Treatmentmentioning
confidence: 99%
“…Uncertainties regarding positive reactions may occur in cases of hidden strongyloidiasis (i.e., low parasite burdens), immunological memory of past infections, or the presence of similar antigens among helminths [104]. In fact, the presence of cross-reactivity with other helminths is considered to be one of the most important limitations in strongyloidiasis immunoassays [101, 105], especially in endemic countries. Conversely, in areas where the infection is uncommon, the detection of specific antibodies is more reliable.…”
Section: S Stercoralis Diagnosis and Treatmentmentioning
confidence: 99%
“…Por outro lado, frações antigênicas derivadas dos estágios evolutivos de ovos e/ou fêmeas parasitas foram descritas por Northern e Grove (1990), Gonçalves et al (2012aGonçalves et al ( , 2012bGonçalves et al ( , 2016 Estudos recentes vêm propondo variações na forma de obtenção de antígenos. Dentre estes pode-se destacar o tratamento com detergentes (Feliciano et al, 2010;Silva et al, 2014), a purificação com o auxílio de colunas Inês et al, 2013;, a utilização de frações de membrana (Corral, et al, 2015a;Paula et al, 2016) e a obtenção dos antígenos de excreção e secreção (Cunha et al, 2017). Teste rápido de diagnóstico para estrongiloidíase (Bon et al, 2010) e técnicas baseadas na produção de antígenos recombinantes (Ravi et al, 2002;Kroleweki et al, 2010;, na metodologia de Phage-display (Feliciano et al, 2014) e na utilização de peptídeos sintéticos (Feliciano et al, 2016) Proteoma pode ser descrito como o conjunto de proteínas expressas a partir de um genoma celular ou de organismos frente a estímulos internos e/ou externos (Padrón;Domont, 2014).…”
unclassified